2 + 1 Highways: Overview and Future Directions. (2nd September 2018) - Romana, Manuel; Martin-Gasulla, Marilo; Moreno, Ana T.
Abstract : Most of the rural transportation system is composed of two-lane highways, and many of them serve as the primary means for rural access to urban areas and freeways. In some highways, traffic volumes can be not high enough to justify a four-lane highway but higher than can be served by isolated passing lanes, or can present high number of head-on collisions. In those conditions, 2 + 1 highways are potentially applicable. This type of highway is used to provide high-performance highways as intermediate solution between the common two-lane highway and the freeway. Successful experiences reported in Germany, Sweden, Finland, Poland, or Texas (US) may suggest that they are potentially applicable in other countries. The objective of this white paper is to provide an overview of the past practice in 2 + 1 highways and discuss the research directions and challenges in this field, specially focusing on, but not limited to, operational research in association with the activities of the Subcommittee on Two-Lane Highways (AHB40 2.2) of the Transportation Research Board. The significance of this paper is twofold: (1) it provides wider coverage of past 2 + 1 highways design and evaluation, and (2) it discusses future directions of this field.